On reification: a reinterpretation of designed and emergent practice - a reply - Paul Joyce; Bernard Lisewski (Association for Learning Technology, 2003)
We welcome the response of Chris Tompsett and Graham Alsop to our article (Lisewski and Joyce, 2003). Within its 'stricter analysis', it is thoughtful and incisive, presenting an interesting critique of our ideas. However, we cannot help but think that the authors have missed the point. Indeed, if we wish to be mischievous we woidd argue that their response is an exemplar of some of the concerns we wanted to raise in our original article